2023
DOI: 10.1101/2023.10.11.23296871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pervasive Influence of Hormonal Contraceptives on the Human Plasma Proteome in a Broad Population Study

Nikola Dordevic,
Clemens Dierks,
Essi Hantikainen
et al.

Abstract: Large-scale plasma proteomics in population studies offer new avenues to explore non-genetic associations, such as biomarkers for lifestyle and environmental exposure. Moreover, through longitudinal monitoring, they help in characterizing the onset and progression of diseases. Utilizing the SWATH DIA-MS-based proteomic approach with 5-minute chromatographic gradients, we examined the neat plasma proteome of 3,632 participants from the Cooperative Health Research in South Tyrol (CHRIS) study. We present precise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…We recently reported that HCU has a major impact on the high abundant fraction of the plasma proteome, in women under 40 years enrolled in the CHRIS study 21 , and as aforementioned, we detected a similar signature in the young women within the BASE-II cohort. With the focus on aging, we herein explored the effect of menopausal hormonal replacement therapy (MHT) in older women participating in the BASE-II.…”
Section: Impact Of Menopausal Hormone Therapy On the High Abundant Se...supporting
confidence: 85%
See 2 more Smart Citations
“…We recently reported that HCU has a major impact on the high abundant fraction of the plasma proteome, in women under 40 years enrolled in the CHRIS study 21 , and as aforementioned, we detected a similar signature in the young women within the BASE-II cohort. With the focus on aging, we herein explored the effect of menopausal hormonal replacement therapy (MHT) in older women participating in the BASE-II.…”
Section: Impact Of Menopausal Hormone Therapy On the High Abundant Se...supporting
confidence: 85%
“…Large-scale serum and plasma proteome studies 21,43,80,81 have revealed disease prevalence, risk factors, and healthcare needs across diverse populations. These studies have identified putative biomarkers of aging 1,[21][22][23][24]80 , common lifestyle factors like Type II Diabetes, and administered drugs 43,82,83 . Advancing age significantly heightens the risk for various chronic ailments alongside physical and cognitive decline, ultimately leading to mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Data generation and processing was described elsewhere. 29 After merging with the genetic data, 3535 participants remained for the analysis ( Suppl. Tab.…”
Section: Methodsmentioning
confidence: 99%
“…When comparing the mass-spectrometry based proteomes of the control (non-PACS) and the PACS group without balancing for these demographic factors, CS components indeed appear to be up-regulated in PACS (Figure 1A). However, the CS is known to be age and BMI dependent ( 7, 8 ). In their data analysis, Cervia-Hasler et al attempt a correction for demographic effects using linear regression ( 5 ).…”
Section: Mainmentioning
confidence: 99%

Role of the complement system in Long COVID

Farztdinov,
Zühlke,
Sotzny
et al. 2024
Preprint
Self Cite